Analysis of deletions in the azoospermia factor region in selected malaysian infertile male subjects - Abd Al-Hussien, Hussein A. (2012)
Infertility is defined as a delay in conception of more than one year duration when there is no use of contraception. Approximately 25% of cases of male infertility are of unknown aetiology. Genetic variations have been found to be as one of the risk factors for male infertility. Among genetic variations, deletions affecting the Azoospermia Factor (AZF) region which is located in the long arm of the Y-chromosome are the most important factors in the development of male infertility. The three types of AZF deletions (AZFa, AZFb and AZFc) have been shown to be associated with male infertility. The frequency rates of those AZF deletions vary among populations due to ethnic factors. Moreover, controversy exists in the literature about the significance of other types of AZF deletions, namely AZFd deletations and partial AZFc deletations (gr/gr, b1/b3, b2/b3 deletions), in male infertility. Conventional Iitiplex PCR-gel electrophoresis is the standard screening method for AZF letions. However, this method has a number of disadvantages as it is a lor-intensive procedure with conflicting results. This study comprised 54 ertile males and 63 fertile controls (proven fertility). The frequency of AZFa, AZFb and AZFc deletions were determined using conventional PCR. In addition, a genetic association study was done to determine the association of AZFd and partial AZFc deletions between male infertility and control subjects. In this study, we have also developed a new real-time PCR High Resolution Melt (HRM) analysis based method to screen for AZF deletions and compared with the results from conventional PCR method. The results of this study showed that, three out of 54 cases (5.55%) had AZF (a, b and c) deletions (two had AZFc and one had AZFa deletions). Four cases were found to have AZFd deletions (7.4%) with two of them were found to be associated with AZFc deletions (p=O.028). In this study, gr/gr deletions were found in six cases (11.53%) as well as in six control subjects (9.52%) and significantly differed (p=O.725). One case was found to have b2/b3 deletion(1.85%, p=O.269) and there were no b1/b3 deletions identified in this study. The new HRM analysis based-method was able to produce the same results obtained with the conventional PCR-gel electrophoresis method. In fact, the HRM based-method was highly repeatable as shown by the 95% Limits of agreement statistical analysis. The frequency of AZF (a, b and c) deletions in Malaysian infertile male subjects was found to be comparable with other populations. AZFd deletions were found to be significant in male infertility and it may be associated with other types of AZF deletions. Partial AZFc deIetions were not found to be significant in Malaysian infertile males. Moreover, the HRM analysis screening method for AZF deletions was found I be reliable, reproducible, fast, probe free, of high throughput, semi¬-automated with easy interpretation of the results and cost-effective method.